Robot-Assisted McKeown Procedure via a Cervical Mediastinoscopy Avoiding an Abdominal and Thoracic Incision - Egberts, Jan-Hendrik; Schlemminger, Mark; Hauser, Charlotte; Becker, Thomas (The Thoracic and Cardiovascular Surgeon, 2019)
Total esophagectomy for esophageal cancer is associated with high morbidity. The avoidance of a thoracic access could especially reduce the occurrence of pulmonary complications. Therefore, the combination of a high transhiatal dissection of the esophagus and a neck access with mediastinal dissection of the esophagus appears to be a possibility to reduce the pulmonary risks. However, the access to the posterior mediastinum is very limited with the conventional minimal invasive instruments. These limitations can be overcome by the use of a surgical robot.In this article, we present a novel operation technique for a complete robot-assisted (da Vinci Xi) McKeown procedure avoiding a thoracic approach and abdominal incision by using a rendezvous technique with an abdominal and cervical docking of the robot system.
Keywords: esophagectomy; RAMIE; robot-assisted; transhiatal; McKeown procedure